Coronary Computed Tomography Angiography Demonstrates a High Burden of Coronary Artery Disease Despite Low‐Risk Nuclear Studies in Pre–Liver Transplant Evaluation. Issue 11 (23rd October 2020) - Löffler, Adrián I.; Gonzalez, Jorge A.; Sundararaman, Shriram K.; Mathew, Roshin C.; Norton, Patrick T.; Hagspiel, Klaus D.; Kramer, Christopher M.; Ragosta, Michael; Rogers, Campbell; Shah, Neeral L.; Salerno, Michael
Abstract : We investigated the presence and severity of coronary artery disease (CAD) in orthotopic liver transplantation (OLT) candidates using coronary artery calcium score (CACS) and coronary computed tomography angiography (CCTA) as compared with the prevalence of normal and abnormal single‐photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI). A total of 140 prospective OLT candidates without known CAD underwent coronary artery calcium (CAC) scans with (n = 77) or without CCTA and coronary computed tomography angiography–derived fractional flow reserve (FFRCT ; n = 57) using a dual‐source computed tomography (CT) and were followed for 2.6 ± 1.4 years. Coronary plaque was quantified using the segment‐involvement score (SIS) and segment stenosis score (SSS). The mean age was 59 ± 6 years, and 65.0% of patients were male. Mean Agatston CACS was 367 ± 653, and 15.0% of patients had CACSs of 0; 83.6% received a SPECT MPI, of which 95.7% were interpreted as normal/probably normal. By CCTA, 9.1% had obstructive CAD (≥70% stenosis), 67.5% had nonobstructive CAD, and 23.4% had no CAD. Nonobstructive CAD was diffuse with mean SIS 3.0 ± 2.9 and SSS 4.5 ± 5.4. Only 14 patients had high risk‐findings (severe 3v CAD, n = 4, CACS >1000 n = 10) that prompted X‐ray angiography in 3 patients who had undergone CCTA, resulting in revascularization of a high‐risk obstruction in 1 patient who had a normal SPECT study. Patients with end‐stage liver disease have a high prevalence of nonobstructive CAD by CCTA, which is undiagnosed by SPECT MPI, potentially underestimating cardiovascular risk. Deferring X‐ray angiography unless high‐risk CCTA findings are present is a potential strategy for avoiding unnecessary X‐ray angiography.